Effect of processing on the antioxidant activity and total phenolic content of some fruits and vegetables commonly consumed by Filipinos. - Dulla, K. A. (Compendium of Human Ecology Researches in the Philippines, 2003)
The effect of boiling, blanching or drying on the antioxidant activity and total phenolic content of 14 different fruits, vegetables, and root crops commonly found in the Filipino diet was investigated. The B-carotene bleaching assay was used to determine the antioxidant activities of the methanolic extracts of the samples. The antioxidant activities of all the root crops including unripe jackfruit (Artocarpus heterophyllus) significantly decreased (22-53%) upon boiling. Blanching green leafy vegetables at different intervals also resulted in the sample's antioxidant activity except for kamote (Ipomoea batatas) leaves. However, the antioxidant activity of commercially prepared dried mango (Magnifera indica) and pineapple (Ananas comosus) were significantly higher than the fresh samples. The total phenolic contents of the methanolic plant extracts were determined using the Folin-Ciocalteau phenolic reagent. All of the boiled samples had significantly lower total phenolic content than fresh samples except for eggplant (Solanum melongena). The blanched leafy green vegetables were also observed to have significant decrease in total phenolic content. Dried mangos and pineapples, consistent with their higher antioxidant activity also had significantly higher total phenolic content than the fresh fruits. Results indicated that different methods of processing plant foods have different effects on its antioxidant activities and phenolic contents.